The interest of 'North Britain': Scottish lobbying, the Westminster Parliament, and the British Union-state, c.1760-c.1830 - Mackley, A (2016)
This thesis is a study of the role of Scots and Scottish society in the politics of the Westminster Parliament and the British Union-state during the later Georgian period. Specifically, it analyses the lobbying activity of certain Scottish interests at Parliament and the central agencies of the British state in London during the period c.1760-c.1830. In doing so, this thesis is concerned with the developing efficacy of Scottish lobbies, as well as the extent to which they represented identifiably Scottish interests at Westminster and within the British Union-state over the course of this period. It aims to expand our understanding of how important elements within Scottish society gradually came to play an active role in the British political centre and argues that Scottish lobbying changed over this period from a position of nurturing and defending a separately constructed Scottish 'national' interest to becoming part of an integrated set of interests operating within a broader and more comprehensive British framework. This change was brought about by the need to represent Scottish interests more effectively within the British Union-state, particularly as the politics of Westminster became more important to certain parts of Scottish society from the 1780s onwards during the early industrial revolution. This process was, at times, uneven, and there was often tension between ongoing convergence and persistent distinction. Nevertheless, Scottish interests became more closely integrated within the British political system over the course of this period through their lobbying activities at the Westminster Parliament and of ministers in Whitehall. They increasingly operated more effectively as part of the British political and legislative process, and did so in ways which no longer presented them as separate or different in what was becoming a more authentically 'British' political culture.